Multiphase Flows in Microfluidics: Fundamentals and Applications - Lin, Jianzhong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This special Issue aimed to collect the latest original research and reviews on the fundamentals and applications of any functional multiphase flow in microfluidics. There were 24 papers submitted to this Special Issue, and 15 papers were accepted. They address numerous topics, mainly on the motion characteristics of particles with different scales and shapes.